Carbon fiber reinforced polypropylene composite material for unmanned aerial vehicle and preparation method thereof

By using carbon fiber reinforced polypropylene composite materials in drone materials, combined with modified carbon fiber and graft modifiers, the problems of low impact toughness, poor thermal conductivity and high flammability of polypropylene materials are solved, and high thermal conductivity is achieved , high mechanical strength and good flame retardant properties, suitable for the application of drone materials.

CN118755198BActive Publication Date: 2024-12-27WEIHAI FORTTECH SCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411047265.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2024-12-27
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

In UAV applications, polypropylene materials have limited performance and service life due to low impact toughness, poor thermal conductivity and high flammability, especially in fire extinguishing scenarios, which have problems such as combustion risks and thermal management of electronic components.

Method used

Using carbon fiber reinforced polypropylene composite material, the thermal conductivity, mechanical strength and flame retardant properties of the material are improved through the use of modified carbon fiber and graft modifiers, compatibility with polypropylene matrix is ​​improved, and optimization is carried out by the addition of paraffin. Lubrication performance.

Benefits of technology

It significantly improves the thermal conductivity, mechanical strength and flame retardancy of composite materials, enhances the oxidation resistance, ensures the stability and long-term use of materials, reduces environmental pollution, and is suitable for the field of drone materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004973825250000031
    Figure BDA0004973825250000031
  • Figure BDA0004973825250000041
    Figure BDA0004973825250000041
  • Figure BDA0004973825250000051
    Figure BDA0004973825250000051
Patent Text Reader

Abstract

The present invention belongs to the technical field of unmanned aerial vehicle materials, specifically a carbon fiber reinforced polypropylene composite material for unmanned aerial vehicle and a preparation method thereof, comprising the following raw materials by weight: 110-130 parts of polypropylene resin, 20-40 parts of modified carbon fiber, 0.3-0.5 parts of initiator and 6-10 parts of paraffin. The prepared composite material is based on polypropylene, and asphalt-based carbon fiber is added as a reinforcing material, which gives the composite material higher thermal conductivity and mechanical strength; by modifying the asphalt-based carbon fiber, the compatibility with the polypropylene matrix is ​​better, the performance is fully utilized, and the grafted modifier can significantly enhance the flame retardancy and oxidation resistance of the material, and the performance is long-term and stable. Therefore, the composite material prepared by the present invention has stable and efficient flame retardancy and oxidation resistance, and good thermal conductivity, high mechanical strength, halogen-free and phosphorus-free, and little environmental pollution, and has important application value in the field of unmanned aerial vehicle material technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of unmanned aerial vehicle materials, and specifically relates to a carbon fiber reinforced polypropylene composite material for unmanned aerial vehicles and a preparation method thereof. Background Art

[0002] Drones, also known as unmanned aerial vehicles, are of many types. According to their size, flight altitude, endurance and load capacity, they can be divided into many types, such as multi-rotor drones, fixed-wing drones and helicopter drones. With the continuous development of science and technology, drones are gradually emerging in the civilian field. Drone materials are gradually transforming towards lightweight, impact-resistant and wear-resistant.

[0003] At present, the basic structural materials of drone fuselage materials mainly include polycarbonate, polyetherimide and polypropylene, etc. Among them, polypropylene (PP) is a lightweight general-purpose plastic with abundant raw materials, low price, simple process and wide application. It is an ideal material for drones, but polypropylene has low impact toughness and large shrinkage rate, which makes polypropylene susceptible to external forces such as stretching, bending and impact during use, resulting in stress whitening. In severe cases, it will also affect the performance and quality of the product, thus limiting its wide application to a certain extent.

[0004] In order to enhance the mechanical strength of polypropylene, carbon fiber is usually added to the material. Carbon fiber is a new type of high-strength, high-modulus fiber material with high strength, low density and excellent electromagnetic properties. It is widely used in high-end fields such as aerospace, military shipbuilding and wind power new energy. The composite material made of polypropylene as the matrix and carbon fiber is light in weight, high in specific stiffness and strength. It can also be made into various shapes and structures in one piece. It is an ideal material for drones.

[0005] In the prior art, when drones are used for firefighting, polypropylene has a low oxygen index and will burn violently when encountering an open flame, causing damage to the internal parts of the drone. In addition, the drone is equipped with complex electronic components, and the thermal conductivity of polypropylene is low, making it difficult to effectively dissipate the heat of the electronic components, thereby affecting the performance and service life of the electronic components. Summary of the invention

[0006] The purpose of the present invention is to provide a carbon fiber reinforced polypropylene composite material for unmanned aerial vehicles and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a carbon fiber reinforced polypropylene composite material for an unmanned aerial vehicle comprises the following steps:

[0009] The polypropylene resin is placed in a blast constant temperature drying oven and dried at 70-80°C for 24-48 hours, and then mixed with modified carbon fiber, initiator and paraffin (lubricant) and put into a twin-screw extruder for melt blending. After extrusion, the mixture is dried in a blast constant temperature drying oven at 70-80°C for 24-48 hours to obtain a carbon fiber reinforced polypropylene composite material for UAV.

[0010] Furthermore, the raw materials are calculated in parts by weight as follows: 110-130 parts of polypropylene resin, 20-40 parts of modified carbon fiber, 0.3-0.5 parts of initiator and 6-10 parts of paraffin wax.

[0011] Furthermore, the initiator is one of benzoyl peroxide and lauroyl peroxide.

[0012] The prepared composite material is based on polypropylene, which gives the material good performance and light weight. Paraffin has good lubrication properties and a low melting point and will be discharged through the exhaust port in the screw. The final composite material does not contain paraffin.

[0013] Further, the modified carbon fiber is prepared by the following steps:

[0014] A1. Add asphalt-based carbon fiber to ethanol solution, ultrasonically treat for 1 hour, add 1-aminopyrene and magnetron, stir for 6 hours at room temperature, react, wash, filter, and finally dry in an oven at 80-100°C for 12 hours to obtain pre-modified carbon fiber;

[0015] A2. Add the pre-modified carbon fiber obtained in step A1 to N,N-dimethylformamide (DMF), disperse it evenly by ultrasonication for 30 minutes, add dicyclohexylcarbodiimide and modifier, slowly heat up to 60°C, start magnetic stirring (speed 1200r / min), stop heating after stirring for 8 hours, cool to room temperature, filter, wash with anhydrous ethanol 3-4 times, and freeze-dry to obtain modified carbon fiber.

[0016] Furthermore, in step A1, the ratio of the amount of asphalt-based carbon fiber, ethanol solution, and 1-aminopyrene is 2 g:100 mL:0.3 g.

[0017] Furthermore, in step A2, the ratio of the amount of N,N-dimethylformamide, the modifier, and dicyclohexylcarbodiimide is 100 mL: 6-12 g: 8.5 g.

[0018] Asphalt-based carbon fibers have the advantages of high thermal conductivity, high modulus, and corrosion resistance, and can improve the thermal conductivity and mechanical strength of composite materials. 1-Aminopyrene is a pyrene molecule containing an amino group, which can have a strong π-π interaction with asphalt-based carbon fibers, and can be stably adsorbed on the surface, introducing amino groups on the carbon fiber surface to provide reaction sites for subsequent reactions.

[0019] Further, the modifier is prepared by the following steps:

[0020] S1. Mix 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine (condensing agent) and toluene in a three-necked flask equipped with a stirring device, heat to 50°C, stir until the solid is completely dissolved, add ethylenediamine, keep warm for 5 hours, and after the reaction is completed, cool naturally, filter, remove the solvent by vacuum distillation, wash with deionized water, and vacuum dry to obtain intermediate 1; the ratio of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine, toluene and ethylenediamine is 23.4g:15mL:100mL:8.1g;

[0021] Under the action of the condensing agent, the amino group on ethylenediamine condenses with the aldehyde group on 3,5-di-tert-butyl-4-hydroxybenzaldehyde to form an imine group (C=N Schiff base structure), and by controlling the molar ratio of the two to be close to 1:1 and a slight excess of ethylenediamine, only one amino group on ethylenediamine participates in the reaction to obtain intermediate 1; the specific reaction process is as follows:

[0022]

[0023] S2. At room temperature, in a three-necked flask equipped with a stirring device, mix the intermediate 1, N,N-dimethylformamide and N,N-diisopropylethylamine (catalyst) evenly under nitrogen protection, place in an ice bath at 5°C, add ethylenetrichlorosilane dropwise, and control the temperature not to exceed 25°C during the addition. After the addition is completed, react at 75°C for 4h. After the reaction is completed, distill under reduced pressure, filter, wash with anhydrous ethanol 3-4 times, and dry in vacuo to obtain intermediate 2; the ratio of intermediate 1, N,N-dimethylformamide, N,N-diisopropylethylamine, and ethylenetrichlorosilane is 55.2g:100mL:30mL:16.4g;

[0024] Under the catalysis of N,N-diisopropylethylamine, intermediate 1 reacts with ethylene trichlorosilane to undergo a nucleophilic substitution reaction. By controlling the molar ratio of the two to be close to 2:1 and a slight excess of ethylene trichlorosilane, only two chlorine groups of ethylene trichlorosilane participate in the reaction to obtain intermediate 2. The specific reaction process is as follows:

[0025]

[0026] S3. At room temperature, in a three-necked flask equipped with a stirring device, add intermediate 2, 4,4'-diaminodiphenyl sulfone, N,N-dimethylformamide and potassium carbonate, mix well, heat to 80°C and keep warm for 6 hours. After the reaction is completed, filter, distill under reduced pressure, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 5:3), remove the eluent by rotary evaporation, and dry in vacuo to obtain intermediate 3; the ratio of the amount of intermediate 2, 4,4'-diaminodiphenyl sulfone, N,N-dimethylformamide and potassium carbonate is 69.8g:24.8g:200mL:15mL;

[0027] Potassium carbonate is used as an acid-binding agent to remove the hydrogen chloride generated by the reaction, and intermediate 2 undergoes a nucleophilic substitution reaction with 4,4'-diaminodiphenyl sulfone to obtain intermediate 3. The specific reaction process is as follows:

[0028]

[0029] S4. Add intermediate 3, succinic acid, dicyclohexylcarbodiimide (DCC, dehydrating agent) and N,N-dimethylformamide to a three-necked flask equipped with a stirring device, stir and mix well, place in a water bath at 55°C, heat in a water bath for 8 hours, and complete the reaction. Filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:3), remove the eluent by rotary evaporation to obtain a modifier; the ratio of the amount of intermediate 3, succinic acid, dicyclohexylcarbodiimide and N,N-dimethylformamide is 90.4g:12.7g:20.6g:200mL;

[0030] Under the action of a dehydrating agent, intermediate 3 undergoes an amidation reaction with succinic acid. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of succinic acid, only one carboxyl group on succinic acid participates in the reaction to obtain a modifier. The specific reaction process is shown below:

[0031]

[0032] One end of the prepared modifier is a carboxyl group, which can react with the amino group on the surface of the pre-modified carbon fiber, and graft organic molecular chains on the surface of the carbon fiber through chemical bonding, that is, an organic layer is formed on its surface, which can greatly improve the interfacial compatibility between the carbon fiber and the polypropylene matrix, thereby promoting the uniform dispersion of the modified carbon fiber in the matrix. Because the asphalt-based carbon fiber has the characteristics of high thermal conductivity and high modulus, it can better exert its performance when uniformly dispersed in the polypropylene matrix, greatly enhancing the thermal conductivity and mechanical strength of the matrix; in addition, carbon fiber is an inorganic material, and the organic modifier grafted on its surface is difficult to seep out and migrate, which improves the long-term stability of the modifier performance; not only that, the modifier molecule is centered on 4,4'-diaminodiphenyl sulfone, which itself has good thermal oxidation resistance, can enhance the thermal oxidation resistance of the polypropylene matrix, and is thermally desulfurized to generate SO2, sulfurous acid and water, which can promote the Fries rearrangement reaction of the matrix, accelerate the carbonization of the matrix, and can effectively increase The flame retardant properties of the matrix are strengthened; in addition, the modifier molecule also contains Si-N flame retardant components, Schiff bases, hindered phenols and carbon-carbon double bond structures, among which the Si-N flame retardant component has the synergistic flame retardant effect of silicon-based and nitrogen-based flame retardants, and compared with the general silicon-based flame retardants in which silicon and oxygen are directly connected, Si-N is a covalent bond, the physicochemical properties are stable, and it is not easy to generate SiO2 during combustion, but to generate a denser Si-C or Si-Si layer, which has better flame retardant and smoke suppression effects; the C=N double bond in the Schiff base structure can generate a carbon-nitrogen six-membered ring at high temperature. This type of six-membered ring structure enables the matrix to form a stable cross-linked network, which synergizes with the Si-N flame retardant component and greatly enhances the flame retardant properties of the matrix; the introduced hindered phenol structure has excellent antioxidant properties, which can not only improve the antioxidant properties of the matrix, but also act as an antioxidant in the production process, avoiding the addition of additional antioxidants and affecting the homogeneity of the composite material; finally, the introduced carbon-carbon double bond can cross-link with the matrix, further improving the stability of the modifier.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The composite material prepared by the present invention uses polypropylene as a matrix and adds asphalt-based carbon fiber as a reinforcing material, which gives the composite material higher thermal conductivity and mechanical strength;

[0035] 2. By modifying the asphalt-based carbon fiber, compared with ordinary asphalt-based carbon fiber, it has better compatibility with the polypropylene matrix, and its performance is fully exerted. The grafted modifier can significantly enhance the flame retardancy and oxidation resistance of the material. At the same time, the performance is long-lasting and stable, and it is not easy to fall off;

[0036] Therefore, the composite material prepared by the present invention has stable and efficient flame retardancy and oxidation resistance, good thermal conductivity, high mechanical strength, is halogen-free and phosphorus-free, has little environmental pollution, and has important application value in the field of UAV material technology. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Embodiment 1

[0039] Preparation of modifier:

[0040] S1. In a three-necked flask equipped with a stirring device, 23.4 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 15 mL of piperidine and 100 mL of toluene were mixed, the temperature was raised to 50° C., and the mixture was stirred until the solid was completely dissolved. 8.1 g of ethylenediamine was added, and the mixture was kept warm for 5 h. After the reaction was completed, the mixture was naturally cooled, filtered, and the solvent was removed by distillation under reduced pressure. The mixture was washed with deionized water and dried under vacuum to obtain intermediate 1.

[0041] S2. At room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, 55.2 g of intermediate 1, 100 mL of N,N-dimethylformamide and 30 mL of N,N-diisopropylethylamine were mixed evenly, placed in an ice bath at 5°C, 16.4 g of ethylenetrichlorosilane was added dropwise, and the temperature was controlled not to exceed 25°C during the addition. After the addition was completed, the reaction was carried out at 75°C for 4 hours. After the reaction was completed, the mixture was distilled under reduced pressure, filtered, washed with anhydrous ethanol 3 times, and dried in vacuo to obtain intermediate 2;

[0042] S3, at room temperature, in a three-necked flask equipped with a stirring device, add 69.8g of intermediate 2, 24.8g of 4,4'-diaminodiphenyl sulfone, 200mL of N,N-dimethylformamide and 15mL of potassium carbonate, mix well, heat to 80°C and keep for 6h, after the reaction is complete, filter, distill under reduced pressure, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 5:3), remove the eluent by rotary evaporation, and dry in vacuo to obtain intermediate 3;

[0043] S4. Add 90.4 g of intermediate 3, 12.7 g of succinic acid, 20.6 g of dicyclohexylcarbodiimide and 200 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, place in a 55°C water bath, heat in a water bath for 8 hours, and when the reaction is completed, filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate in a volume ratio of 4:3), remove the eluent by rotary evaporation, and obtain a modifier.

[0044] Embodiment 2

[0045] Preparation of modifier:

[0046] S1. In a three-necked flask equipped with a stirring device, 46.8 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 30 mL of piperidine and 200 mL of toluene were mixed, the temperature was raised to 50° C., and the mixture was stirred until the solid was completely dissolved. 16.2 g of ethylenediamine was added, and the mixture was kept warm for 5 h. After the reaction was completed, the mixture was naturally cooled, filtered, and the solvent was removed by distillation under reduced pressure. The mixture was washed with deionized water and dried under vacuum to obtain intermediate 1.

[0047] S2. At room temperature, in a three-necked flask equipped with a stirring device, 110.4 g of intermediate 1, 200 mL of N,N-dimethylformamide and 60 mL of N,N-diisopropylethylamine were mixed evenly under nitrogen protection, and then placed in an ice bath at 5°C, and 32.8 g of ethylenetrichlorosilane was added dropwise, and the temperature was controlled not to exceed 25°C during the addition. After the addition was completed, the reaction was carried out at 75°C for 4 hours. After the reaction was completed, the mixture was distilled under reduced pressure, filtered, washed with anhydrous ethanol 4 times, and dried in vacuo to obtain intermediate 2;

[0048] S3, at room temperature, in a three-necked flask equipped with a stirring device, add 139.6 g of intermediate 2, 49.6 g of 4,4'-diaminodiphenyl sulfone, 400 mL of N,N-dimethylformamide and 30 mL of potassium carbonate, mix well, heat to 80°C and keep for 6 hours, the reaction is complete, filter, distill under reduced pressure, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 5:3), remove the eluent by rotary evaporation, and dry in vacuo to obtain intermediate 3;

[0049] S4. Add 180.8 g of intermediate 3, 25.4 g of succinic acid, 41.2 g of dicyclohexylcarbodiimide and 400 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, place in a water bath at 55°C, heat in a water bath for 8 hours, and after the reaction is completed, filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:3), remove the eluent by rotary evaporation to obtain a modifier.

[0050] Embodiment 3

[0051] Preparation of modified carbon fiber:

[0052] A1. 2 g of asphalt-based carbon fiber was added to 100 mL of ethanol solution. After ultrasonic treatment for 1 h, 0.3 g of 1-aminopyrene and magnetron were added. The mixture was stirred for 6 h at room temperature until the reaction was complete. The mixture was washed, filtered, and finally dried in an oven at 80-100 ° C for 12 h to obtain pre-modified carbon fiber.

[0053] A2. Add the pre-modified carbon fiber obtained in step A1 to 100 mL of N,N-dimethylformamide, disperse evenly by ultrasonication for 30 min, add 8.5 g of dicyclohexylcarbodiimide and 6 g of the modifier obtained in Example 1, slowly heat to 60 ° C, turn on magnetic stirring (speed 1200 r / min), stop heating after stirring for 8 h, cool to room temperature, filter, wash 3 times with anhydrous ethanol, and freeze-dry to obtain modified carbon fiber.

[0054] Embodiment 4

[0055] Preparation of modified carbon fiber:

[0056] A1. 2 g of asphalt-based carbon fiber was added to 100 mL of ethanol solution. After ultrasonic treatment for 1 h, 0.3 g of 1-aminopyrene and magnetron were added. The mixture was stirred for 6 h at room temperature until the reaction was complete. The mixture was washed, filtered, and finally dried in an oven at 80-100 ° C for 12 h to obtain pre-modified carbon fiber.

[0057] A2. Add the pre-modified carbon fiber obtained in step A2 to 100 mL of N,N-dimethylformamide, disperse evenly by ultrasonication for 30 min, add 8.5 g of dicyclohexylcarbodiimide and 12 g of the modifier obtained in Example 2, slowly heat to 60 ° C, turn on magnetic stirring (speed 1200 r / min), stop heating after stirring for 8 h, cool to room temperature, filter, wash 3 times with anhydrous ethanol, and freeze-dry to obtain modified carbon fiber.

[0058] Embodiment 5

[0059] 110 g of polypropylene resin was placed in a blast constant temperature drying oven and dried at 70° C. for 24 h, then mixed with 20 g of the modified carbon fiber prepared in Example 3, 0.3 g of benzoyl peroxide and 6 g of paraffin wax and put into a twin-screw extruder for melt blending. After extrusion, the mixture was dried in a blast constant temperature drying oven at 70° C. for 24 h to obtain a carbon fiber reinforced polypropylene composite material for drones.

[0060] Embodiment 6

[0061] 120 g of polypropylene resin was placed in a blast constant temperature drying oven and dried at 75° C. for 36 hours, and then mixed with 30 g of the modified carbon fiber prepared in Example 4, 0.4 g of lauroyl peroxide and 8 g of paraffin wax and put into a twin-screw extruder for melt blending. After extrusion, the mixture was dried in a blast constant temperature drying oven at 75° C. for 36 hours to obtain a carbon fiber reinforced polypropylene composite material for drones.

[0062] Embodiment 7

[0063] 130 g of polypropylene resin was placed in a blast constant temperature drying oven and dried at 80° C. for 48 h, and then mixed with 40 g of the modified carbon fiber prepared in Example 4, 0.5 g of lauroyl peroxide and 10 g of paraffin wax and put into a twin-screw extruder for melt blending. After extrusion, the mixture was dried in a blast constant temperature drying oven at 80° C. for 48 h to obtain a carbon fiber reinforced polypropylene composite material for drones.

[0064] Comparative Example 1

[0065] An equal amount of common asphalt-based carbon fiber was used to replace the modified carbon fiber in Example 7, and the remaining steps were the same as in Example 7 to prepare a composite material.

[0066] Comparative Example 2

[0067] Commercially available carbon fiber reinforced polypropylene composites were used.

[0068] Example 5-7 and Comparative Example 1-2 were made into corresponding shapes according to different test standards and subjected to the following performance tests:

[0069] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to measure the limiting oxygen index of the sample before and after being placed at room temperature for 180 days;

[0070] The oxidation induction time was determined using the national standard GB / T 19466.6-2009 "Plastic Differential Scanning Calorimetry";

[0071] The tensile strength was determined using the national standard GB / T 1040-2006 "Determination of tensile properties of plastics";

[0072] The notched impact strength is measured using the national standard GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics";

[0073] The thermal conductivity of the composite material was measured using a TPS2500S thermal constant analyzer under the following test conditions: 25°C, heating time <5 min, heating power <100 mV;

[0074] The measurement results are shown in the following table:

[0075]

[0076]

[0077] It can be seen from the above table that the composite material prepared in the embodiment of the present invention has higher flame retardancy and antioxidant properties than the comparative example, and has good thermal conductivity, high mechanical strength, and long-term stable performance, and has important application value in the field of UAV material technology.

[0078] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0079] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A carbon fiber reinforced polypropylene composite material for drones, characterized in that: The invention comprises the following raw materials in parts by weight: 110-130 parts of polypropylene resin, 20-40 parts of modified carbon fiber, 0.3-0.5 parts of initiator and 6-10 parts of paraffin wax; Wherein, the modified carbon fiber is prepared by the following steps: A1. Add asphalt-based carbon fiber to ethanol solution, ultrasonically treat for 1 hour, add 1-aminopyrene and magnetron, stir for 6 hours at room temperature, and complete the reaction. Wash, filter and dry to obtain pre-modified carbon fiber; A2, adding the pre-modified carbon fiber obtained in step A1 to DMF, dispersing evenly by ultrasonication for 30 min, adding dicyclohexylcarbodiimide and modifier, heating to 60° C., turning on magnetic stirring, stirring for 8 h, cooling, filtering, washing, and drying to obtain modified carbon fiber; The modifying agent is prepared by the following steps: S1. Mix 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine and toluene, heat to 50°C, stir until the solid is completely dissolved, add ethylenediamine, keep warm for 5 hours, and after the reaction is completed, cool naturally, filter, distill under reduced pressure, wash, and vacuum dry to obtain intermediate 1; S2, at room temperature, under nitrogen protection, mix intermediate 1, DMF and N,N-diisopropylethylamine evenly, place in a 5°C ice bath, add ethylenetrichlorosilane dropwise, react at 75°C for 4h, and after the reaction is complete, distill under reduced pressure, filter, wash, and dry in vacuo to obtain intermediate 2; S3, mixing intermediate 2, 4,4'-diaminodiphenyl sulfone, DMF and potassium carbonate, reacting at 80°C for 6 hours, filtering, distilling under reduced pressure, purifying by column chromatography, rotary evaporation and drying to obtain intermediate 3; S4. After stirring the intermediate 3, succinic acid, dicyclohexylcarbodiimide and DMF, heat at 55°C for 8 hours. After the reaction is completed, filter, distill under reduced pressure, purify by column chromatography, and rotary evaporate to obtain a modifier.

2. The carbon fiber reinforced polypropylene composite material for drone according to claim 1, characterized in that: In step S1, the ratio of the amount of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine, toluene and ethylenediamine is 23.4 g: 15 mL: 100 mL: 8.1 g.

3. The carbon fiber reinforced polypropylene composite material for drone according to claim 1, characterized in that: In step S2, the ratio of the amount of intermediate 1, DMF, N,N-diisopropylethylamine, and ethylenetrichlorosilane is 55.2 g:100 mL:30 mL:16.4 g.

4. The carbon fiber reinforced polypropylene composite material for drone according to claim 1, characterized in that: In step S3, the ratio of the amount of intermediate 2, 4,4'-diaminodiphenyl sulfone, DMF and potassium carbonate is 69.8 g: 24.8 g: 200 mL: 15 mL.

5. The carbon fiber reinforced polypropylene composite material for drone according to claim 1, characterized in that: In step S4, the ratio of the amount of intermediate 3, succinic acid, dicyclohexylcarbodiimide and DMF is 90.4 g:12.7 g:20.6 g:200 mL.

6. The carbon fiber reinforced polypropylene composite material for drone according to claim 1, characterized in that: In step A1, the ratio of the amount of asphalt-based carbon fiber, ethanol solution, and 1-aminopyrene is 2 g:100 mL:0.3 g.

7. The carbon fiber reinforced polypropylene composite material for drone according to claim 1, characterized in that: In step A2, the ratio of DMF, modifier and dicyclohexylcarbodiimide is 100 mL: 6-12 g: 8.5 g.

8. The method for preparing a carbon fiber reinforced polypropylene composite material for unmanned aerial vehicles according to claim 1, characterized in that: The following steps are involved: After the polypropylene resin is dried, it is mixed with modified carbon fiber, initiator and paraffin and then put into a twin-screw extruder for melt blending. After extrusion and drying, a carbon fiber reinforced polypropylene composite material for drones is obtained.